Optimisation of estrogen receptor subtype-selectivity of a 4-Aryl-4H-chromene scaffold previously identified by virtual screening. Issue 5 (1st March 2020) - Carr, Miriam; Knox, Andrew J.S.; Nevin, Daniel K.; O'Boyle, Niamh; Wang, Shu; Egan, Billy; McCabe, Thomas; Twamley, Brendan; Zisterer, Daniela M.; Lloyd, David G.; Meegan, Mary J.
Graphical abstract: Abstract: 4-Aryl-4 H -Chromene derivatives have been previously shown to exhibit anti-proliferative, apoptotic and anti-angiogenic activity in a variety of tumor models in vitro and in vivo generally via activation of caspases through inhibition of tubulin polymerisation. We have previously identified by Virtual Screening (VS) a 4-aryl-4 H -chromene scaffold, of which two examples were shown to bind Estrogen Receptor α and β with low nanomolar affinity and <20-fold selectivity for α over β and low micromolar anti-proliferative activity in the MCF-7 cell line. Thus, using the 4-aryl-4 H -chromene scaffold as a starting point, a series of compounds with a range of basic arylethers at C-4 and modifications at the C3-ester substituent of the benzopyran ring were synthesised, producing some potent ER antagonists in the MCF-7 cell line which were highly selective for ERα (compound 35 ; 350-fold selectivity) or ERβ (compound 42 ; 170-fold selectivity).